PELAYANAN PENGELOLAAN LABORATORIUM MENGGUNAKAN QR CODE BERBASIS GOOGLE FORM - Hanna Nurul Husna; Syifa Nursiswanti; Iis Rahmawati; Cucu Nurpatonah; Ai Meri Yulianti; Itmam Milataka; Nurul Zakiatul Jannah Fitriani (Jurnal Abdi Insani, 2023)
QR code is a technology that is currently developing rapidly. Currently, laboratory services in the Refraction Optics Study Program are still carried out conventionally. The application of technology in laboratory management is needed to increase effectiveness and efficiency. The purpose of this activity is to create and implement a QR code in laboratory services. The QR code is used in the form of borrowing laboratory equipment; as well as record the use of equipment and laboratory space activities. The method used in this activity is the design method. The laboratory service form is created using Google Form and a QR code is created. Student responses to the application of the use of the QR code were obtained using a questionnaire. Data were analyzed descriptively. A total of five QR codes integrated with Google Form and Google Sheets have been created. The QR code includes a form for borrowing equipment and using the laboratory space. QR code in laboratory services has been successfully implemented. Some of the advantages of this laboratory digitization activity are unique, efficient, paperless, and easy to collect data. However, several shortcomings were found, such as high dependence on the internet, form displays that were still complex and less than simple. The use of QR codes in laboratory services raises pros and cons. The use of QR codes in the lab can be evaluated and integrated with other media to make it more attractive. Socialization and adaptation to the use of the QR code and in laboratory services are needed.